Glasses for subjects whose eyes are provided with myopia control protocols and related methods - GIRIEDT, G; SPIEGEL DAVID (2023)
Eyewear (1) for a subject whose eye is provided with a myopia control scheme, the myopia control scheme causing a change over time of an eye characteristic of the eye, the eyewear comprising:-at least one ophthalmic lens (100), at least one ophthalmic lens having an adjustable optical feature to be placed in front of the eye of the subject to improve vision of the subject; -a control unit (200) comprising one or more memories (220) and one or more processors (210) and adapted to control said ophthalmic lens by setting said adjustable optical characteristic to a current value (CV); the one or more memories have stored therein data (221) relating to the temporal variation of the eye feature of the eye, the one or more processors programmed to determine the current value of the adjustable optical feature based on the data. 一种用于眼睛被提供了近视控制方案的受试者的眼镜(1)，所述近视控制方案引起了所述眼睛的眼特征的随时间变化，所述眼镜包括：-至少一个眼科镜片(100)，该至少一个眼科镜片具有可调光学特征、将被放置在所述受试者的所述眼睛的前方以改善所述受试者的视力；-控制单元(200)，该控制单元包括一个或多个存储器(220)和一个或多个处理器(210)，并且适于通过将所述可调光学特征设定为当前值(C